Wine consumption in the city of Recife (Brazil): a study of the relevance of the drink’s attributes on the moment of purchase - Diniz, Nayara (2017)
This study is a theoretical-empirical research on the identification and analysis of wine attributes’ relevance in the purchase decision process to consumers from Recife. The theoretical framework was developed based on the identification of the most-frequently evaluated wine attributes in consumer behaviour studies in several countries. Subsequently, based on the work of Goodman et al. (2007), the relevance degree of each attribute was classified through the Best-Worst Scaling (BWS). The methodological approach was quantitative in nature, the data collection method was a questionnaire adapted from Forbes (2008) and Groot (2011) and completed by 100 consumers. The results show that price, brand, awards, alcohol by volume and attractive front label were considered important attributes by the consumers. However, the decisive attributes for the purchase decision were others: grape variety, country of origin of the wine, food harmonization and the information on the back label.